Nursing as a Public Trust Profession - Iwona Czerwińska Pawluk; Anna Dębska; Walery Zukow (Journal of Education, Health and Sport)
Introduction. Nursing is widely recognized as a public trust profession due to its emphasis on professionalism, ethical standards, and patient-centered care. The profession demands adherence to legal regulations and ethical norms, fostering trust through its critical role in healthcare delivery. This study aims to explore patients' perceptions of nursing as a public trust profession, focusing on key factors such as professionalism, ethical compliance, and personal attributes of nurses.